Ownership concentration, corporate risk-taking and performance: Evidence from Vietnamese listed firms - Tran Nam Hoai; Chi Dat Le (Cogent Economics & Finance, 2020)
This study examines the associations of corporate governance with firm risk-taking and performance in a typical frontier equity market characterized by high ownership concentration and weak investor protection. Using an extensive sample of Vietnamese listed firms, we find (1) no relation between ownership concentration and firm profitability, but a non-linear relation between ownership concentration and firm valuation; and (2) that concentrated ownership increases the riskiness of accounting performance; however, there is no evidence of the linkage between concentration and the riskiness of market performance. Ultimately, our findings confirm essential differences in using the two alternatives of performance measurement.
Keywords: 330; corporate governance; ownership structure; firm performance; risk-taking; Vietnam